2017
DOI: 10.1097/ta.0000000000001360
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Intestinalis Predictive Evaluation Study

Abstract: Prognostic study, level II; therapeutic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A recent prospective multicenter trial examined 127 adults who were found on computed tomography to have pneumatosis 128. Investigators prospectively collected information on comorbidities, clinical presentation, and other imaging findings that might predict which patients with pneumatosis had or would develop transmural ischemia.…”
Section: Imagingmentioning
confidence: 99%
“…A recent prospective multicenter trial examined 127 adults who were found on computed tomography to have pneumatosis 128. Investigators prospectively collected information on comorbidities, clinical presentation, and other imaging findings that might predict which patients with pneumatosis had or would develop transmural ischemia.…”
Section: Imagingmentioning
confidence: 99%
“…Conversely, radiological patterns did not appear to be as useful in distinguishing pathologic PI from benign PI in the context of other independent predictors. Furthermore, the decreased level of hemoglobin, could reflect a sloughing of the mucosa as an effect of necrosis which leads to gastrointestinal bleeding [ 28 ] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conservative approach is allowed in a stable patient with no signs of complications [2]. In the presence of predictive factors of pathologic PCI, namely transmural ischemia and bowel perforation, surgical procedure is required [9].…”
Section: Discussionmentioning
confidence: 99%